Comprehensive analysis of putative dihydroflavonol 4-reductase gene family in tea plant - Mei, Xin (PLoS One, 2019)
One identified dihydroflavonol 4-reductases (DFR) encoding gene (named as CsDFRa herein) and five putative DFRs (named as CsDFRb1, CsDFRb2, CsDFRb3, CsDFRc and CsDFRd) in tea (Camellia sinensis) have been widely discussed in recent papers concerning multi-omics data. However, except for CsDFRa, their function and biochemical characteristics are not clear. This study aims to compare all putative CsDFRs and preliminarily evaluate their function. We investigated the sequences of genes (coding and promoter regions) and predicted structures of proteins encoded, and determined the activities of heterologously expressed CsDFRs under various conditions. The results showed that the sequences of five putative CsDFRs were quite different from CsDFRa, and had lower expression levels as well. The five putative CsDFRs could not catalyze three dihydroflavonol substrates. The functional CsDFRa had the strongest affinity with dihydroquercetin, and performed best at pH around 7 and 35°C but was not stable at lower pHs or higher temperatures. Single amino acid mutation at position 141 modified the preference of CsDFRa for dihydroquercetin and dihydromyricetin, and also weakened its stability. These data suggest that only CsDFRa works in the pathway for generating anthocyanidins and catechins. This study provides new insights into the function of CsDFRs and may assist to develop new strategies to manipulate the composition of tea flavonoids in the future.